Implementing reading interventions to support disadvantaged children in England: insights from a process evaluation. Issue 6 (19th September 2022) - Wood, Audrey B.; Price, Jayne; Salter, Emma; Woodhouse, Fiona; Zsargo, Liz
ABSTRACT: In this paper, we present insights from the qualitative data collected during a process evaluation of a reading intervention project carried out in primary and secondary schools in West Yorkshire, England. Commercially available reading interventions, financed by the Strategic School Improvement Fund, were delivered by school staff to disadvantaged pupils over a period of four half-terms, and a team of university-based researchers carried out qualitative interviews with members of school staff in order to discover factors that affect the sustainability of school-based reading interventions after the initial funding period, and identify good practice in planning for and meeting sustainability objectives. The data from the interviews enabled the researchers to compare and contrast the experiences of the staff following the different interventions. The findings presented in this paper have generated some helpful guidance about the process of implementing reading interventions in schools successfully, and factors such as staff training, fidelity of implementation and organisational context are discussed.